Pengembangan Model Perilaku Mencuci Tangan Pada Mahasiswa Untuk Pemulihan Kesehatan Lingkungan Kampus Pasca Pandemi Covid-19 - Esthi Kusdarini; Agus Budianto (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
The face-to-Face teaching-learning process required several preparations to prevent the re-emergence of Covid-19. Students are the majority of campus inhabitants involved in the teaching-learning process, so compliance in implementing healthy protocols is very important. Hand washing is one of the health protocols which must be carried out because it is an important activity. This research aimed to develop a model of handwashing behaviour and examine the effects of knowledge variables (Z1), attitudes (Z2), and the facilities of soap, water, and hand sanitiser (Z3) on the handwashing behaviour (Y). Model examine used a set of empirical data collected from 101 chemical engineering students randomly. Then, the writers collected, sorted, and analysed the data statistically using descriptive statics, multiple linear regression test, T-test, and F test. Data representation, validation, and data correlation were conducted in MS Excel and SPSS 20. Multiple linear regression test produced the equation of Y = 3.722 + 0.035Z1 + 0.142Z2 + 0.269Z3 + e. The T-test showed that knowledge was not partially affecting handwashing behaviour; both attitude and facilities, each behaviour affected handwashing behaviour partially. The F test explained that knowledge, attitudes, and facilities simultaneously affected hand wash behaviour. Determination coefficient testing of the model showed that knowledge, attitudes, and facilities of soap, water, and hand sanitiser gave 48.3% contribution from all variables which influenced handwashing behaviour. The development of handwashing behaviour could be conducted by providing the stimuli like socialising the importance of handwashing (through posters, banners, and counselling between lecturing) and providing soap, water, and hand sanitiser facilities on campus corners. It involved the students in the socialisation and provided the handwashing facilities.